Дослідження вмісту гідроксикоричних кислот у моркви коренеплодах у залежності від терміну їх зберігання - Zhuravel, Iryna; Burda, Nadiia; Kyslychenko , Viktoriia (Annals of Mechnikov’s Institute, 2026)
Introduction. Carrot (Daucus carota L.) from the Celery family (Apiaceae) is cultivated in many countries of the world as a vegetable crop. Carrot root crops are consumed fresh and processed. In Ukraine, the varieties of this crop Yaskrava, Nantska Kharkivska, Olenka are mainly grown, which are included in the State Register of Plant Varieties Suitable for Distribution in Ukraine. Carrots are root vegetables with high nutritional, therapeutic and prophylactic value and the possibility of long-term storage. The chemical composition of root crops is represented by phenolic compounds, in particular flavonoids, hydroxycinnamic acids, tannins, steroids, triterpenoids, polyacetylenes, carbohydrates, vitamins and provitamins, mineral complexes. Phenolic compounds, in particular hydroxycinnamic acids, deserve special attention. These substances exhibit antioxidant, cardioprotective, hepatoprotective, anti-inflammatory, anticancer activity, improve digestion, cardiovascular and nervous system functions. Therefore, hydroxycinnamic acids are valuable nutrients of carrot, a root crops, due to which this raw material is a useful food and therapeutic and prophylactic product. The study of the content of biologically active hydroxycinnamic acids depending on the primary processing of the raw material and its storage period is relevant. The aim of the work was to determine the quantitative content of hydroxycinnamic acids in carrot root crops of the Yaskrava, Nantska Kharkivska and Olenka varieties depending on their storage period. Materials and methods. The objects of the study were carrot root crops of the varieties Yaskrava, Nantska Kharkivska, Olenka. The raw materials were harvested at the end of October 2025 in the Kharkiv region (Ukraine). After harvesting, the root crops were separated from the above-ground part, washed in cold water, dried, small roots were removed and stored in a refrigerator at a temperature of +7-8 °C for 3 months. For the experiment with fresh carrot root crops, samples were taken after 1, 2 and 3 months of storage, the raw materials were cut with a knife into strips measuring 1.0´0.5 cm and dried in a drying cabinet at a temperature of 45-50 °C. The content of hydroxycinnamic acids was determined by spectrophotometric method according to the method of the national part of the monograph "Nettle Leaves" of the State Pharmacopoeia of Ukraine 2.0.3. The results obtained were processed by the method of mathematical statistics. Results and discussion. According to the literature, it is known that technological processing of carrot root crops causes stress and stimulates the accumulation of hydroxycinnamic acids. We investigated minimally technologically processed raw materials of three varieties of carrots, which are mainly cultivated in Ukraine. As a result of the research, it was found that during the first month of storage of carrot root crops of all studied varieties, an increase in the content of hydroxycinnamic acids was observed several times, which did not contradict the literature data. The record holder for the accumulation of hydroxycinnamic acids in the underground organs of carrot after the first month of storage was the Nantska Kharkivska variety (2.66 ± 0.05 %). In root crops of the Yaskrava variety, the content of the studied compounds increased by 3.5 times, in the Nantska Kharkivska variety - by 3.8, and in the Olenka variety - by 3.6 times. During further storage of carrot root crops, the content of hydroxycinnamic acids decreased slightly. After 2 months, the content of hydroxycinnamic acids in raw carrot raw materials of the Yaskrava variety decreased within the deviation limits, after 3 months - by 0.13 ± 0.01 %. Root crops of the Nantska Kharkivska variety lost 3.76 % of hydroxycinnamic acids in the 2nd month of storage, and 6.77 % in the 3rd month compared to the 1st month. In raw carrot variety Olenka, the decrease in the content of the studied phenolic acids was 6.57 % in the 2nd month and 13.13% in the 3rd month of storage. The decrease in the content of hydroxycinnamic acids in carrot root crops at 3 months of storage compared to 2 months for all studied varieties was insignificant. Conclusions. As a result of determining the quantitative content of hydroxycinnamic acids in carrot root crops of the Yaskrava, Nantska Kharkivska and Olenka varieties, an increase in the content of these compounds in the studied raw material by 3.5-3.8 times was found after 1 month and a slight decrease in their content after 2 and 3 months of root crop storage at a temperature of +7-8 °C. Therefore, carrot root crops of the studied domestic varieties of selection can be a useful source of nutrients necessary for the human body, in particular hydroxycinnamic acids, during long-term storage, which will certainly improve the quality of nutrition of the broad population of our country.